Direction of translation and textual cohesion: A study of two Spanish translations of The Analects using Coh-Metrix-Esp - Liu, Zhao; Sun, Ce (Círculo de Lingüística Aplicada a la Comunicación, 2024)
This study set out to investigate the effect of direction in textual cohesion. It compares two Spanish translations of 论语 (The Analects) from Chinese, one by a non-native translator and the other by a native translator. Using Coh-Metrix-Esp, both translations are analyzed at the lexical, syntactical, and textual levels to evaluate the overall textual cohesion. The results confirmed an effect of direction in translation: translation conducted by a native speaker is more coherent and easier to read than that by a non-native translator. However, some parameters revisited also suggest that non-native translator can be more successful in some respects. Our conclusion is that there is no apparent advantage of a native translator over a non-native translator.